2014
DOI: 10.1902/jop.2014.130577
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Association Between Smoking and Periodontitis in the Dunedin Study With an Enhanced Analytical Approach

Abstract: The smoking-periodontitis association is observable with hierarchical modeling, providing strong evidence that chronic smoking is a risk factor for periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 23 publications
4
46
0
3
Order By: Relevance
“…Cannabis use was associated with attachment loss, which can result in tooth loss. 26,36 A similar association was observed for tobacco use, consistent with previous research. 26,36,51 Tobacco’s effect on periodontal disease is thought to be mediated through increased inflammation and vasoconstriction, 51 which may or may not be the case for cannabis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cannabis use was associated with attachment loss, which can result in tooth loss. 26,36 A similar association was observed for tobacco use, consistent with previous research. 26,36,51 Tobacco’s effect on periodontal disease is thought to be mediated through increased inflammation and vasoconstriction, 51 which may or may not be the case for cannabis.…”
Section: Discussionsupporting
confidence: 91%
“…26,36 A similar association was observed for tobacco use, consistent with previous research. 26,36,51 Tobacco’s effect on periodontal disease is thought to be mediated through increased inflammation and vasoconstriction, 51 which may or may not be the case for cannabis. Cannabis use was not associated with systemic inflammation here or elsewhere, 30,39 but prior research has shown that cannabis can induce vasoconstriction.…”
Section: Discussionsupporting
confidence: 91%
“…Controlling for “destination SES” (that is, in adulthood) did make a difference, most notably for those oral disease characteristics with either a considerable “filled” component to them (such as DMFT and root DFS) or a more recent pattern of development (such as root DS or periodontitis). The latter is heavily influenced by recent smoking, and that is strongly associated with age‐38 SES in this cohort . Arguably, though, we should not control for SES in adulthood in this study, given that childhood IQ is itself an important predictor of SES in adulthood (in the Dunedin cohort, the mean standardized childhood IQ scores in the high, medium and low age‐38 SES groups were 108.8, 99.2 and 92.2, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Users of multiple illicit drugs have poorer periodontal status. This association has been found among drug users without crack cocaine use, 33–35 when the main drug was heroin, 36 , 37 methamphetamine, 15 , 16 marijuana, 38 and cocaine 13 , 30 . Evidence has demonstrated individuals dependent on illicit drugs rarely restrict themselves to only one type of drug during the course of their dependence 39 .…”
Section: Discussionmentioning
confidence: 95%